SISTEM INFORMASI AKUNTANSI UTANG USAHA BERBASIS SAP (SYSTEM APPLICATION AND PRODUCT IN DATA PROCESSING) PADA PT. KIMIA FARMA TBK - Neng Syifaa Rose Liana (2021)
ABSTRACT The field work practice activity which was carried out for three months from February to April aims to find out how the accounting information system of PT. Kimia Farma Tbk, especially in the accounts payable section. To obtain relevant information on trade payables, interviews and direct observations were made at the field work practice, conducting a review of trade payables starting from purchasing raw material loans to paying off trade payables at PT. Kimia Farma Tbk directly assists the implementation of trade payables in the company. Implementation of transactions PT. Kimia Farma Tbk uses SAP software as a support in every transaction, especially accounts payable. Starting from the purchase of credit to payments to suppliers PT. Kimia Farma Tbk uses SAP as a support for the company's operations, of course it is related to its information system. SAP used by PT. Kimia Farma Tbk is also very influential on the flow of accounts payable in the company, so that PT. Kimia Farma Tbk has always succeeded in reducing the number of errors in recording its accounts payable. With this final report, it can be concluded that PT. Kimia Farma Tbk doing trade payables already using modern applications that have effectiveness in the implementation of debt in accordance with the provisions of applicable accounting standards and procedures. Therefore, the author wants to discuss how the SAP-based accounts payable information system at PT Kimia Farma Tbk.